For an inclusive rural education: appreciations of Ramiro Guerra - Pereira Castellón, Adrián Francisco (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: This article aims to characterize, based on Ramiro Guerra's appreciations, the educational problems of the Cuban peasant population in the 1940s. During this period, rural society received special attention and projects for higher primary schools were promoted. Originality/contribution: We consider this research relevant because it reveals, through the educational thought and biography of a barely explored character, one of the manifestations of alienation of the Cuban peasantry, which would be the basis of the social and political fights led by the progressive movements and Cuban revolutionaries between the 40s and 50s of the last century. Method: In this work, documentary, biographical and hemerographic research is used. All these duly based on historical-logical and analytic-synthetic methods. The reconstruction of biographical information about Ramiro Guerra Sánchez is rooted in his context of action. This was only possible by consulting public documentary collection repositories that grant access to hemerographic sources. Strategies: search and organization of documents from the National Library of Cuba and the Digital Collection of the University of Florida. Conclusion: this article allows the characterization of the educational situation in the Cuban rural population in the 40's of the last century and also allows to deepen in the analysis of the educational ideas that Ramiro Guerra contributed to that social group. It is also an opportunity to appraise the progressiveness of Guerra Sanchez's thought.